Role of the small RNA RyhB in the Fur regulon in mediating the capsular polysaccharide biosynthesis and iron acquisition systems in Klebsiella pneumoniae - Huang, Su-Hua; Wang, Chien-Kuo; Peng, Hwei-Ling; Wu, Chien-Chen; Chen, Ying-Tsong; Hong, Yi-Ming; Lin, Ching-Ting (My University, 1970)
"Background: The capsular polysaccharide (CPS) and iron acquisition systems are important determinants of Klebsiella pneumoniae infections, and we have previously reported that the ferric uptake repressor (Fur) can play dual role in iron acquisition and CPS biosynthesis. In many bacteria, Fur negatively controls the transcription of the small non-coding RNA RyhB to modulate cellular functions and virulence. However, in K. pneumoniae, the role played by RyhB in the Fur regulon has not been characterised. This study investigated Fur regulation of ryhB transcription and the functional role of RyhB in K. pneumoniae. Results: Deletion of fur from K. pneumoniae increased the transcription of ryhB; the electric mobility shift assay and the Fur-titration assay revealed that Fur could bind to the promoter region of ryhB, suggesting that Fur directly represses ryhB transcription. Additionally, in a Delta fur strain with elevated CPS production, deletion of ryhB obviously reduced CPS production. The following promoter-reporter assay and quantitative real-time PCR of cps genes verified that RyhB activated orf1 and orf16 transcription to elevate CPS production. However, deletion of ryhB did not affect the mRNA levels of rcsA, rmpA, or rmpA2. These results imply that Fur represses the transcription of ryhB to mediate the biosynthesis of CPS, which is independent of RcsA, RmpA, and RmpA2. In addition, the Delta fur strain's high level of serum resistance was attenuated by the deletion of ryhB, indicating that RyhB plays a positive role in protecting the bacterium from serum killing. Finally, deletion of ryhB in Delta fur reduced the expression of several genes corresponding to 3 iron acquisition systems in K. pneumoniae, and resulted in reduced siderophore production. Conclusions: The regulation and functional role of RyhB in K. pneumoniae is characterized in this study. RyhB participates in Fur regulon to modulate the bacterial CPS biosynthesis and iron acquisition systems in K. pneumoniae."
Keywords: RyhB; Fur; Capsular polysaccharide; Iron acquisition system; Klebsiella pneumoniae